Making the most of irrigation to reduce Africa's deficit - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
workshop on irrigation schemes in sub-Saharan Africa, in Harare from April 25-29, 1988 CTA in collaboration with the International Institute for Land Reclamation and Improvement (ILRI) of the Netherlands